Mitochondrial Adaptations of Obese Adult Rat Visceral Adipocytes which Differ in Nutritional Status during Childhood - Lailan Safina Nasution; Ahmad Aulia; Sri Widia A. Jusman; Mohamad Sadikin (Faculty of Medicine Universitas Indonesia, 2021)
Mitochondria are highly dynamic organelles that can adapt to different environmental stimuli. This study aims to analyze differences in the function and biogenesis of mitochondria and anaerobic glycolysis activity between obese adult rats that were undernourished in childhood (LCD28) and those which were normal (SD28) or already fat (HFD28). Sprague-dawley rats were assigned groups and given diet treatments from December 2017 until August 2018 in the Laboratory Animal Management Unit, Faculty of Veterinary Medicine, Bogor Agricultural Institute. To observe mitochondrial function and biogenesis, MnSOD activity and PGC1α levels were analyzed using ELISA. To investigate the existence of anaerobic glycolysis, LDH activity was analyzed using a spectrophotometry method. The results showed that MnSOD activity and PGC1α levels of LCD28 increased compared to the other groups, signifying higher mitochondrial function and biogenesis. Meanwhile, no significant difference in LDH activity was found, signifying similar levels of anaerobic glycolysis.